Career Paths and Professional Experiences of Alumni: A Tracer Study - Jamili, Evangeline (JPAIR Multidisciplinary Research, 2026)
The Graduate Tracer Survey carefully analyzes career paths, professional experiences, and insights of alumni to inform strategic institutional improvements. Grounded in the Human Capital Theory (Becker, 1964) and Super’s Career Development Theory (Super, 1980), the study employed a descriptive survey design, collecting quantitative and qualitative data from 266 graduates via an online structured questionnaire. Results clearly demonstrate strong alumni employability and the direct relevance of the school’s education. A strong 83.5% of respondents are employed full-time, with 56.6% securing their first job within 6 months of graduation. Over half of the respondents, (60.6%) found jobs directly related to their degrees, mostly in accounting and finance. Alumni are mostly employed in the government (43.5%) and local private organizations (35.9%), with an impressive 86.9% reporting self-employment. These findings conclude that SPSPS effectively cultivates valuable human capital, resulting in a high rate of graduate employability and direct career relevance. The study recommends continuous curriculum review to integrate emerging technologies and enhance career counseling and strengthened industry linkages to further optimize graduate success and institutional alignment with dynamic workforce needs.